Easy extraction of Ganoderma boninense liquid sample using portable on‐chip device - Adella Josephin; Yudan Whulanza; Siti Fauziyah Rahman; Kenny Lischer; Muhammad Imam Surya; Irfan Martiansyah; Wiguna Rahman; Uda Hashim (Indonesian Journal of Biotechnology, 2024)
Detecting Ganoderma boninense in Indonesia is crucial for effectively controlling and mitigating the spread of basal stem disease in oil palm fields. While there is ongoing development of tolerant plants, no such plant has been successfully created yet. Consequently, researchers are actively studying detection methods for Ganoderma boninense. One established and highly accurate approach is the use of polymerase chain reaction (PCR) techniques for molecular detection. However, this method requires time‐consuming sample preparation, which can pose challenges in plantation settings. To address this problem, a portable lab‐on‐chip device has been introduced. This technology enables easy and automatic DNA retrieval from liquid samples by absorbing lysed DNA using magnetic beads. An efficient mechanism for manipulating the magnetic bead within the semiconductor has been successfully implemented. The extraction process typically takes around 15 minutes using a modified methodology on the chip device approach. The chip facilitates the retrieval of two samples with a capacity of 120 µL for each sample. The PCR method was utilized to validate the equivalence of the lab‐on‐chip device extraction to the standard extraction method. This represents a promising alternative for expedited and simplified detection of Ganoderma boninense in field conditions.